2005
DOI: 10.1093/ndt/gfi005
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine stress echocardiography and the resting but not exercise electrocardiograph predict severe coronary artery disease in renal transplant candidates

Abstract: In selecting which potential renal transplant candidates should undergo coronary angiography, resting ECG and dobutamine stress echocardiography are the best predictors of severe CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 20 publications
1
115
0
Order By: Relevance
“…56 Clinical risk stratification and coronary angiography predicted MACEs after a median follow-up of 46 months, but results of MPS and DSE did not. Several observational studies reported an increased unadjusted risk of all-cause mortality and MACEs in patients with angiographic CAD, 55,58 whereas other investigations identified excess risk in only certain patient subgroups such as those with proximal CAD 57 or with nondiabetic renal failure. 59 Several recent studies have found no associations of CAD with subsequent patient survival.…”
Section: Imperfect Correlations Of Angiographic Cad and Clinical Outcmentioning
confidence: 99%
“…56 Clinical risk stratification and coronary angiography predicted MACEs after a median follow-up of 46 months, but results of MPS and DSE did not. Several observational studies reported an increased unadjusted risk of all-cause mortality and MACEs in patients with angiographic CAD, 55,58 whereas other investigations identified excess risk in only certain patient subgroups such as those with proximal CAD 57 or with nondiabetic renal failure. 59 Several recent studies have found no associations of CAD with subsequent patient survival.…”
Section: Imperfect Correlations Of Angiographic Cad and Clinical Outcmentioning
confidence: 99%
“…Our rate of indeterminate tests was high (35.5%), and a large proportion of these patients were unable to achieve adequate HR elevation, reflecting poor exercise tolerance of ESRD patients which has previously been demonstrated (34). Some prospective trials (35,36) have demonstrated an indeterminate result alone as a significant independent predictor of death (arrhythmic and nonarrhythmic), but the relevance in ESRD patients remains to be assessed.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the sensitivity and specificity of exercise electrocardiography in CKD/ESRD patients is poor (Table 1). 13,14 Similarly, the sensitivity and specificity of myocardial perfusion single photon emission computed tomography (SPECT) to detect CAD in CKD/ESRD patients are highly variable. In a prospective study of 138 patients referred for pre-renal transplant cardiac evaluation (43% on dialysis) and underwent coronary artery calcium score, coronary computer tomography angiography, and SPECT, SPECT had a low sensitivity (53%) and modest specificity (82%) for detecting obstructive CAD (C50% stenosis).…”
Section: Stress Test In Ckd/esrd Patientsmentioning
confidence: 99%